PEMBERDAYAAN PERPUSTAKAAN BANK INDONESIA PROVINSI KALIMANTAN BARAT - yarso, Chairiyah; Latifa Hanum, Atiqa Nur (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEmpowerment is an important part of library management because libraries have a role as a means of education, research, preservation, information, and recreation. This study aims to discuss the implementation of library empowerment activities and obstacles encountered. This is a descriptive research using qualitative methods. The data were collected from five informants using interviews, observation, and documentation techniques. The findings showed that the Bank Indonesia Library of Kalimantan Barat has conducted six of seven library empowerment criteria such as improvement of the quality and professionalism of managers, library infrastructure, library collections, library promotion, collaboration between libraries, and budget making. Along with the activities, several obstacles found were the slow response to the questionnaire for the needs of library material analysis, the tight schedule of employees, library materials that were not by the educational background of all the internship students, and the absence of additional service variations. Therefore, as one effort of library empowerment, libraries can use marketing strategies in the form of information package services in the form of concise packaging of information.Â Keywords: Library empowerment, Specific library, Bank Indonesia